Molecular characterization of heavy metal tolerant bacteria from an agricultural soil - Ilusanya, Olusolape Afolake Favour; Olajumoke, Oluwasegun Irouoghene; Fogbonja, Oyindolapo Christianah; Egberongbe, Haneefat Olabimpe; Oyeyipo, Funmilayo Mujidat; Yakubu, Reuben (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2024)
The aim of this study was to isolate and characterize heavy metal tolerant bacteria from an agricultural soil in Ago Iwoye, Ogun Stae, Nigeria. Bacteria were isolated from soil samples collected and screened for tolerance to different concentrations of lead, copper and cadmium. Heavy metal tolerant bacteria were characterized using phenotypic and molecular techniques. All the isolates were able to grow and tolerate different concentration of the heavy metals while four isolates identified as Bacillus cereus, Pseudomonas aeruginosa, Altantibacter hermannii and Enterobacter quasihormaechei exhibited high degree of tolerance to Pb, Cu and Cd with minimum inhibitory concentrations of 1500mg/l of lead,1000mg/l of Cu and 700mg/l of Cd. These results highlighted the high potential of these bacteria as bioremediation tools of heavy metal contaminated soil.Keywords: Heavy metal, tolerance, bacteria, agricultural soil